Chemical synthesis of magnesium niobate powders - Srisombat L. (2014)
Magnesium niobate (MgNb2O6) powders in orthorhombic form have been successfully prepared via an oxalate synthetic route. Solutions of magnesium chloride hexahydrate and niobium pentachloride were used as the starting materials in the synthesis of MgNb2O6 powders. The formation mechanism of MgNb2O6 was clarified by TG-DTA, FT-IR and X-ray diffraction (XRD). The morphology of the formed powders was examined by scanning electron microscopy (SEM). It was found that the second phases of MgO, Nb2O5 and Mg0.66Nb 1.33O29 tend to form together with MgNb2O 6, depending on calcination conditions. However, single-phase MgNb2O6 powders consisting of nanoparticles 100-300 nm were successfully obtained for a calcination temperature of 750 °C for 13 h with the introduction of pre-firing (750 °C/2 h) and remixing processes. © 2003 Elsevier B.V. All rights reserved.